IMPLEMENTATION OF STUNTING PREVENTION PROGRAM POLICY IN PANGKEP REGENCY - Anita Reski Amalia; Eritrina Eritrina (JURNAP: Jurnal Administrasi Publik, 2026)
Stunting is one of the targets of the Sustainable Development Goals (SDGs), including Sustainable Development Goal 2, namely eliminating hunger and all forms of malnutrition. This study aims to analyze the implementation of stunting prevention program policies in Pangkep Regency. This study uses a qualitative method with a phenomenological approach. Data collection was carried out through observation, interviews, and documentation, while data analysis was carried out through the stages of data collection, data condensation, data presentation, and drawing and verifying conclusions. The results of the study indicate that the implementation of stunting prevention policies has been running quite well, although there are still several aspects that have not been implemented optimally. The success of policy implementation was analyzed using the MSN Policy Implementation Model, which includes mentality, system, and networking approaches. In the mentality approach, Health Office officials have demonstrated a good commitment and understanding of the urgency of the stunting problem, which is reflected in their attitudes and concrete steps in implementing prevention programs. However, in terms of responsibility, obstacles were still encountered in the form of changes and reductions in budget allocations from 2021 to 2022. Furthermore, in 2023, the management of the Special Allocation Fund (DAK) for the stunting program was transferred to the Population and Family Planning Control Agency (DPPKB). In the system approach , policy implementation has been carried out in accordance with Pangkep Regent Regulation Number 23 of 2020. However, cultural factors in the community, such as parenting patterns that do not comply with recommended practices and the high risk of early marriage that has the potential to cause low birth weight (LBW), remain challenges in stunting prevention efforts. In the networking approach, a strategic partnership with Dompet Dhuafa has made a positive contribution, particularly in supporting the acceleration of the Open Defecation Free (ODF) declaration.